Molecular identification of grouper species using PCR-RFLP technique. (May 2015) - Sumathi, G.; Jeyasekaran, G.; Jeya Shakila, R.; Sivaraman, B.; Arunkumar, G.; Manimaran, U.; Sukumar, D.
Abstract: A PCR-RFLP method was used to identify five species of raw and processed groupers belonging to the genus, Epinephelus viz. E . areolatus, E . bleekeri, E . faveatus, E . longispinis and E . undulosus . DNA extracted from all the species using phenol-chloroform method amplified the mt 16S rRNA gene, unique for the genus, Epinephelus, using GenF and EpiR primers at 300 bp. This fragment did not amplify the DNA of even closely related grouper genus, Cephalopholis, making the method more specific the grouper genus, Epinephelus . The specificity was further ascertained by performing the internal control that targeted 18S rRNA, which was eukaryotic specific. Digestion of PCR products with three selected restriction enzymes viz. SduI, BciVI, and Sau3AI followed by PAGE yielded species specific patterns that enabled identification of three grouper species viz. E . bleekeri, E . faveatus and E . longispinis, while the other two species viz. E . areolatus and E . undulosus gave similar pattern in the gel, although minor variations in the molecular sizes of digested products were noticed. Chilled, frozen and cooked groupers also gave similar PCR-RFLP pattern to that of raw groupers making this method suitable even for processed products. Highlights: Molecular identification of grouper species using PCR-RFLP technique. DNA extraction. Amplification of mitochondrial 16S rRNA gene fragment. DNA sequencing and selection of restriction enzymes. PCR-RFLP analysis.